Stepping Up Skills for More Jobs and Higher Productivity - World Bank (Washington, DC, 2017)
This report presents a framework - Skills Toward Employment and Productivity (STEP), that provides a simple yet comprehensive way to look at skills development. It brings together research evidence and practical experience from a range of areas-from research on the determinants of early childhood development and learning outcomes, to policy experience with the reform of vocational and technical education systems and labor markets-and provides a set of powerful messages to policymakers, researchers, and practitioners. The report's emphasis on performance measurement and benchmarking, policy and program evaluation, and cross-sectoral approaches focusing on individuals throughout their lifecycle provides a solid platform for developing countries to start exploring reforms.